Online laboratories: Spaces of remote education and possible contributions to integral human training in basic education (Research, Society and Development, 2022)
The use of Information and Communication Technologies (ICTs) has become essential in the activities of education institutions through remote teaching with the suspension of face-to-face classes due to the Covid-19 pandemic. Due to difficulties in accessing traditional laboratories for carrying out practices by basic education students, it has become essential to use remote and virtual laboratories to carry out practices, which can be accessed via the internet regardless of the geographical location of the students, a series of these have been developed by some institutions, the Federal University of Santa Catarina (UFSC) stands out through the research group of the Remote Experimentation Laboratory (RexLab). This new context began to demand research on projects aimed at the integration of ICTs in basic education from the perspective of integral human formation. This article aims to report on successful experiences of projects aimed at the use of educational technologies that use remote and virtual laboratories aimed at high school in order to apply practices of applied science disciplines, developed by the RExLab research group at UFSC with support from the National Council for Scientific and Technological Development (CNPQ).